Sensory and bio-chemical preservation of ricotta cheese using natural products - Asensio, Claudia Mariana (2014)
The objective of this study was to evaluate the antimicrobial activity and to study their preserving effect on quality and sensory parameters on flavoured ricotta cheese of Argentinean oregano essential oils (EOs). Criollo essential oil was the most effective agent controlling foodborne bacteria, with MIC values of 1.90 E-04 mg mL 1 for S. aureus and Salmonella sp. Ricotta with Cordobes essential oil exhibited the lowest percentage of lactic acid at the end of the storage (0.246%). After 30 days of storage, ricotta flavoured with Cordobes and Criollo EOs had the lowest total count (5.63 9 103 and 7.80 9 103 cfu g 1 , respectively). The Pearson’s correlation analyses (P ≤ 0.05) showed that sour flavour was negatively related to cheese and casein flavours (r = 0.46 and 0.52, respectively). The inclusion of oregano EOs into ricotta cheese improves quality parameters but affects its sensory attributes.